Occurrence of 3-MCPD fatty acid esters in human breast milk - Zelinková, Zuzana; Novotný, Oldřich; Schůrek, Jakub; Velíšek, Jan; Hajšlová, Jana; Doležal, Marek (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2008)
A series of twelve breast milk samples were analysed by gas chromatography-mass spectrometry (GC/MS) operated in selected ion monitoring mode for 3-chloropropane-1,2-diol (3-MCPD). Whilst none of the samples contained 3-MCPD above the limit of detection of 3 microg kg(-1) milk, all contained high amounts of 3-MCPD esterified with higher fatty acids. The levels of 3-MCPD released by hydrolysis of these esters (bound 3-MCPD) ranged from the limit of detection (300 microg kg(-1), expressed on a fat basis) to 2195 microg kg(-1); with a mean level of bound 3-MCPD of 1014 microg kg(-1), which corresponded to 35.5 microg kg(-1) milk. The presence of bound 3-MCPD was confirmed using orthogonal gas chromatography coupled with high-speed time-of-flight mass spectrometry analysis for four randomly selected breast milk samples. Six breast milks collected from one of the nursing mothers 14-76 days after childbirth contained bound 3-MCPD within the range of 328-2078 microg kg(-1) fat (mean 930 microg kg(-1) fat). The calculated bound 3-MCPD content of these samples was within the range of 6 and 19 microg kg(-1) milk (mean of 12 microg kg(-1) milk). The major types of 3-MCPD esters were the symmetric diesters with lauric, palmitic, and oleic acids, and asymmetric diesters with palmitic acid/oleic acid among which 3-chloro-1,2-propanediol 1,2-dioleate prevailed.
Keywords: financování organizované; dospělí; alpha-Chlorohydrin; Female; Adult; ženské pohlaví; Food Contamination; Adolescent; lipidy; Food Analysis; mateřské mléko; alfa-chlorhydrin; lidé; Lipids; Financing, Organized; Milk, Human; kontaminace potravin; analýza potravin; plynová chromatografie s hmotnostně spektrometrickou detekcí; Gas Chromatography-Mass Spectrometry; mladiství; Humans